Implementasi Metode ABC (Activity Based Costing) Untuk Menentukan Tarif Pengiriman Barang Pada J&T Express Pekanbaru - Fionasari, Dwi; Hetri Suriyanti, Linda; Ramashar, Wira; Samsiah, Siti; Syaf Putra, rudi; Agustiawan, Agustiawan; Fathurrahmi Lawita, Nadia; Simme, Ervina (LPPM UMRI, 2022)
Devotion discusses how to calculate the tariff for shipping goods using the ABC (Activity Based Costing) method on J&T Express Pekanbaru. When J&T Express implements the ABC method, the company will be able to find out the right and accurate shipping rates by using cost triggers from the company's operational activities. This research is a qualitative research with a comparative descriptive design, comparing the shipping rates that have been used by the company with the rates using the ABC method. The results of the research using ABC show that there is a lower tariff in the category in the destination city of Pekanbaru. Researchers suggest that companies use tariff calculations using the ABC method in order to avoid errors in determining shipping rates.